Intravenous Vitamin C in Adults with Sepsis in the Intensive Care Unit - Lamontagne, François; Masse, Marie-Hélène; Menard, Julie; Sprague, Sheila; Pinto, Ruxandra; Heyland, Daren K.; Cook, Deborah J; Battista, Marie-Claude; Day, Andrew G.; Guyatt, Gordon H.; Kanji, Salmaan; Parke, Rachael; et al. (The New England journal of medicine, 2022)
In this trial of intravenous vitamin C in adult patients with sepsis, those who received a vitamin C infusion had a higher risk of death or persistent organ dysfunction at 28 days than those who received placebo.